Affective Commitment And Self-Efficacy As Mediators In The Relationship Between Transformational Leadership And Employee Performance - Ahmad Rais Habib; Muhaidir Ikram; Josafat Gracia Ginting (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study aims to examine the influence of transformational leadership on affective commitment and self-efficacy, as well as its influence on the performance of junior high school teachers in Baraka District, Enrekang Regency, South Sulawesi Province. This aims to provide an overview of variables that have been researched, namely the variables of transformational leadership, affective commitment, self-efficacy, and performance. The descriptive verification method is a method used by researchers to test the truth of the proposed hypothesis by collecting empirical data obtained in the field. To prove the theory, this study utilizes data collected through a survey and examines it with both descriptive and inferential statistics, as well as Structural Equation Modeling analysis. Assisted by the AMOS 24 program. The results of the study: (1) Transformational leadership influences affective commitment, (2) Transformational leadership influences self-efficacy, (3) Transformational leadership influences performance, (4) Affective commitment does not influence performance, and (5) Self-efficacy influences performance.